Effectiveness of preoperative plasmapheresis in a pregnancy complicated by hyperthyroidism and anti-thyroid drug-associated angioedema. (May 2013) - Ekiz Bilir, B.; Soysal Atile, N.; Kirkizlar, O.; Kömürcü, Y.; Akpinar, S.; Sezer, A.; Demir, M.; Hekimoğlu, S.
Abstract Hyperthyroidism is not a rare entity in pregnancy and 85% of these cases attributed to Graves' disease (GD). There is no therapeutic modality for GD considered as totally safe in pregnancy. Fetal and neonatal risks of maternal hyperthyroid disease are related to the hyperthyroidism itself and/or to the medical treatment of the disease. There are no data supporting an association between congenital anomalies in the fetus and propylthiouracil (PTU). Hepatotoxicity, cytopenias – especially agranulocytosis and quite rarely, angioedema, may be seen as side effects of PTU. In this case report, we examine an instance of Graves' hyperthyroidism diagnosed during pregnancy. In this case, a serious side effect during anti-thyroid drug usage was encountered, eventually resulting in surgery in the second trimester. This intervention was assisted by the use of plasmapheresis to obtain rapid normalization of serum thyroid hormone levels.